Application of aluminum-modified food waste biochar as adsorbent of fluoride in aqueous solutions and optimization of production using response surface methodology - Meilani, Vera; Lee, Jae In; Kang, Jin Kyu; Lee, Chang Gu; Jeong, Sanghyun; Park, Seong Jik (Microporous and Mesoporous Materials, 2021)
Adsorption of fluoride from aqueous solutions by aluminum-impregnated biochar derived from food waste (Al-FWB) was studied. The individual and interactive effects of various factors on fluoride adsorption, including pyrolysis temperature and time, and aluminum content, were investigated. The optimum conditions for the synthesis of Al-FWB, predicted through a Box–Behnken-based response surface methodology model, which were as follows: a temperature of 315 °C, time of 0.65 h (39 min), and an aluminum content of 5.89%. Batch experiments were conducted to assess the feasibility of using Al-FWB for fluoride removal, and its mechanism. The Langmuir isotherm model and pseudo-second-order kinetics proved to be the best fit for the equilibrium data, with a maximum adsorption capacity of 123.4 mg/g. Thermodynamic results revealed a spontaneous endothermic reaction for fluoride adsorption. The Al-FWB showed a superior removal efficiency (91.4%) in a wide pH range (5–11) due to its pH buffering capacity during the adsorption process. The influence of co-existing anions on the fluoride adsorption was as follows: PO43‾ > SO42‾ > HCO3‾ > NO3‾. Therefore, Al-FWB can be used as an effective adsorbent to remove fluoride from aqueous solutions.
Keywords: Adsorption capacities; Endothermic reactions; Langmuir isotherm models; pH buffering capacity; Pseudo second order kinetics; Pyrolysis temperature; Removal efficiencies; Response surface methodology; Adsorption; Aluminum; Biochar; Fluoride removal; Food waste; Response surface methodology